Children and Young People’s Participation in Decision-Making Within Healthcare Organisations in New Zealand: An Integrative Review - Foster, Mandie; Blamires, Julie; Moir, Chris; Jones, Virgina; Shrestha- Rangit, Jagamaya; Dickinson, Annette (SAGE Publications, 2023)
There is a paucity of literature on children and young people’s participation in decision-making within healthcare organisations in New Zealand. This integrative review examined child self-reported peer-reviewed manuscripts and published guidelines, policy, reviews, expert opinion and legislation to explore how New Zealand children and young people participate in discussions and decision-making processes within healthcare settings and what are barriers and benefits to such participation. Four child self-reported peer-reviewed manuscripts and twelve expert opinion documents were retrieved from four electronic databases including academic, government and institutional websites. Inductive content thematic analysis generated one theme (a discourse in children and young people’s participation within healthcare settings), four sub-themes, 11 categories, 93 codes and 202 findings. It is evident within this review that there is a discourse between what expert opinion are stating is required to promote children and young people’s participation in discussions and decision-making processes within healthcare settings and what is occurring in practice. Despite literature reporting on how children and young people’s participation and voice were essential for healthcare provision, there was sparse literature published on children and young people’s participation in discussions and decision-making processes in healthcare delivery in New Zealand.
Keywords: child advocacy; children’s participation; children’s rights; determination of healthcare needs; healthcare systems; 4203 Health Services and Systems; 42 Health Sciences; Pediatric; 7.1 Individual care needs; 7 Management of diseases and conditions; 7.3 Management and decision making; Generic health relevance; 1110 Nursing; 1114 Paediatrics and Reproductive Medicine; 1117 Public Health and Health Services; 3213 Paediatrics; 4205 Nursing